Answer:
the answer is 1/45
Step-by-step explanation:
just use the proportion method
Answer:
see below
Step-by-step explanation:
The exponent rules that apply are ...
(a^b)(a^c) = a^(b+c)
a^-b = (1/a)^b
(a^b)^c = a^(b·c)
_____
These let you rewrite the given function as ...
f(x) = (3^(2x))(3^1) = 3(3^(2x)) = 3(3^2)^x = 3·9^x
and
f(x) = 3^(2x+1) = (3^-1)^(-(2x+1)) = (1/3)^-(2x+1)
Answer:
36
Step-by-step explanation:
When you multiply -6 x -6 you get 36.
Hope this helps:)
Answer:
a) yes
b) 2560
Step-by-step explanation:
An exponential function has a common ratio between points uniformly spaced. Here, the data points are 10 years apart.
The ratio of the first two values is 4000/5000 = 0.8.
The ratio of the next two values is 3200/4000 = 0.8.
These ratios are the same, so the data is consistent with an exponential function.
The common ratio can be used to predict the next value. The next value is predicted to be ...
3200 × 0.8 = 2560